1997
DOI: 10.1007/s002510050281
|View full text |Cite
|
Sign up to set email alerts
|

PA28 subunits of the mouse proteasome: primary structures and chromosomal localization of the genes

Abstract: The 20S proteasome is a multi-subunit protease responsible for the production of peptides presented by major histocompatibility complex (MHC) class I molecules. Recent evidence indicates that an interferon-gamma (IFN-gamma)-inducible PA28 activator complex enhances the generation of class I binding peptides by altering the cleavage pattern of the proteasome. In the present study, we determined the primary structures of the mouse PA28 alpha- and beta-subunits. The deduced amino acid sequences of the alpha- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…These results indicate that PA28␥ is unlikely to play a pivotal role in the MHC class I antigen processing/presentation system. This is consistent with the observation that PA28␥ has been found in invertebrates that do not have the adaptive immune system (26). However, the present study does not rule out the possibility that PA28␥ plays a specialized role in antigen presentation such as the processing of antigens in the nucleus.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results indicate that PA28␥ is unlikely to play a pivotal role in the MHC class I antigen processing/presentation system. This is consistent with the observation that PA28␥ has been found in invertebrates that do not have the adaptive immune system (26). However, the present study does not rule out the possibility that PA28␥ plays a specialized role in antigen presentation such as the processing of antigens in the nucleus.…”
Section: Discussionsupporting
confidence: 87%
“…Construction of the PA28␥ Targeting Vector-A 12-kb NotI fragment containing the entire coding region of the PA28␥ gene was obtained from a 129/SvJ mouse genomic library (Stratagene) as previously reported (26,27). The targeting vector consisted of the 6.2-kb genomic DNA containing the 1.2-kb neomycin resistance gene derived from pMC1neopoly(A) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought to play an important role in the production of MHC class I antigenic peptides (Groettrup et al, 1996). PA28␥, initially called "Ki antigen," is similar to PA28␣ and ␤ (Kandil et al, 1997;Tanahashi et al, 1997), but forms only homoheptamers and is mostly nuclear. Its functions are poorly characterized, but studies in mice (Murata et al, 1999;Barton et al, 2004) and flies (Masson et al, 2003) suggest a role for this complex in cell cycle progression and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse (Kandil et al, 1997) this gene is tightly linked to Psme1 and Psme2 which have been shown to be highly expressed in lung, spleen and liver tissue in pig (Wang et al, 2004) suggesting that ATP5G1 might be related to animal immunity.…”
Section: Resultsmentioning
confidence: 99%